Scaling Printable Zn–Ag2O Batteries for Integrated Electronics. Issue 13 (21st February 2019) - Kumar, Rajan; Johnson, Kevin M.; Williams, Nicholas X.; Subramanian, Vivek
Abstract: Printed batteries are an emerging solution for integrated energy storage using low‐cost, high accuracy fabrication techniques. While several printed batteries have been previously shown, few have designed a battery that can be incorporated into an integrated device. Specifically, a fully printed battery with a small active electrode area (<1 cm 2 ) achieving high areal capacities (>10 mAh cm −2 ) at high current densities (1–10 mA cm −2 ) has not been demonstrated, which represents the minimum form‐factor and performance requirements for many low‐power device applications. This work addresses these challenges by investigating the scaling limits of a fully printed Zn–Ag2 O battery and determining the electrochemical limitations for a mm 2 ‐scale battery. Processed entirely in air, Zn–Ag2 O batteries are well suited for integration in typical semiconductor packaging flows compared to lithium‐based chemistries. Printed cells with electrodes as small as 1 mm 2 maintain steady operating voltages above (>1.4 V) at high current densities (1–12 mA cm −2 ) and achieve the highest reported areal capacity for a fully printed battery at 11 mAh cm −2 . The findings represent the first demonstration of a small, packaged, fully printed Zn–Ag2 O battery with high areal capacities at high current densities, a crucial step toward realizing chip‐scale energy storage for integrated electronic systems. Abstract : Scaling limits for a fully printed Zn–Ag2 O battery are explored to develop on‐chip energy storage for integrated electronics. With 1 mm 2 electrodes, the printed Zn–Ag2 O batteries demonstrate high areal capacities (11 mAh cm –2 ) at device‐relevant current densities. These batteries have thin form‐factors and utilize low processing temperatures, making them compatible with low‐cost, flexible substrates and emerging silicon integration strategies.